2015
DOI: 10.1007/s12199-015-0501-3
|View full text |Cite|
|
Sign up to set email alerts
|

High-risk mesothelioma relation to meteorological and geological condition and distance from naturally occurring asbestos

Abstract: Objectives Very few studies have investigated the incidence and risk of malignant mesothelioma (MM) associated with distinct sources of asbestos exposure, especially exposure to naturally occurring asbestos (NOA). Methods Subjects were MM, lung, and breast cancer patients who were diagnosed and followed in Diyarbakir Province between 2008 and 2013. The birthplaces of patients were displayed on a geologic map. Geological and meteorological effects on MM were analyzed by logistic regression. Results A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…It is known that the concentration of asbestos fibers in the air surrounding the emission point depends on wind direction and velocity (Laamane et al 1965 ). Abakay et al ( 2016 ) studied the risk of developing environmental mesothelioma for inhabitants near naturally occurring asbestos (NOA) source. They found that the distance of a residence from NOA and the predominant wind direction can influence the MM risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the concentration of asbestos fibers in the air surrounding the emission point depends on wind direction and velocity (Laamane et al 1965 ). Abakay et al ( 2016 ) studied the risk of developing environmental mesothelioma for inhabitants near naturally occurring asbestos (NOA) source. They found that the distance of a residence from NOA and the predominant wind direction can influence the MM risk.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years and in several countries the health investigations dealing with asbestos moved from the occupational to environmental exposure (e.g., Baumann et al, 2015;Abakay et al, 2016;Noonan, 2017). According some authors in fact the exposure to low but continuous exposure, as in the case of inhabitants of houses next to the asbestos bearing rock outcrops (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to other elongated mineral particles. Other elongated mineral particles such as erionite or fluoro-edenite may be involved in the aetiology of malignant mesothelioma (Supplementary Material, Table S4) [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94], with potential environmental exposure in various countries, such as Turkey, USA and Mexico [95][96][97].…”
Section: Mesothelioma Aetiologymentioning
confidence: 99%